THE INFLUENCE OF HEALTH PROFESSIONALS ON THE CHOICE TO USE SIGN LANGUAGE - Layane Rocha de Lima; Maria Clara Souza Rodrigues da Silva; Camila Correia Firmino; Givânya Bezerra de Melo; Gabrielle Leite Pacheco Lisbôa (Cogitare Enfermagem, 2022)
Objective: to understand how the conduct of health professional’s influences (or does not influence) parents and/or guardians in choosing the use of sign language after the diagnosis of deafness.